Answer:
208 calories
Step-by-step explanation:
You have to divide 624 by 3, and you get 208.
Scale factor is given by:
(length of larger figure)/(length of smaller figure)=(width of larger figure)/(width of the smaller figure)=3.4
The length of the larger figure will be given by:
length=(scale factor)*(length of smaller figure)
=3.4*6=20.4 cm
width of the larger figure will be given by:
width=(scale factor)*(width of smaller figure)
=3.4*4.5
=15.3 cm
Therefore the dimension of the new parallelogram will be 20.4 cm by 15.3 cm
Answer:
y=1.2x-3
Step-by-step explanation:
I had this as an rsm problem a few weeks ago and forgot how to solve it lol hope this helps
The vertex form of a quadratic function is:
f(x) = a(x - h)² + k
The coordinate (h, k) represents a parabola's vertex.
In order to convert a quadratic function in standard form to the vertex form, we can complete the square.
y = 2x² - 5x + 13
Move the constant, 13, to the other side of the equation by subtracting it from both sides of the equation.
y - 13 = 2x² - 5x
Factor out 2 on the right side of the equation.
y - 13 = 2(x² - 2.5x)
Add (b/2)² to both sides of the equation, but remember that since we factored 2 out on the right side of the equation we have to multiply (b/2)² by 2 again on the left side.
y - 13 + 2(2.5/2)² = 2(x² - 2.5x + (2.5/2)²)
y - 13 + 3.125 = 2(x² - 2.5x + 1.5625)
Add the constants on the left and factor the expression on the right to a perfect square.
y - 9.875 = 2(x - 1.25)²
Now, we need y to be by itself again so add 9.875 back to both sides of the equation to move it back to the right side.
y = 2(x - 1.25)² + 9.875
Vertex: (1.25, 9.875)
Solution: y = 2(x - 1.25)² + 9.875
Or if you prefer fractions
y = 2(x - 5/4)² + 79/8
Answer:
It's like solving a quadratic, but in reverse, and in this case you'll arrive at x2+x−12=0
Explanation:
We're going to go "backwards" with this problem - normally we're asked to take a quadratic equation and find the roots. So we'll do what we normally do, but in reverse:
Let's start with the roots:
x=3, x=−4
So let's move the constants over with the x terms to have equations equal to 0:
x−3=0, x+4=0
Now we can set up the equation, as:
(x−3)(x+4)=0
We can now distribute out the 2 quantities:
x2+x−12=0